Modified Stirrup Brace (MSB)の紹介 : 脳卒中患者の自転車駆動への応用を目的として - 渡辺 敏; 山田 純生; 安田 慎一 (理学療法学, 1988)
脳卒中片麻痺患者における自転車駆動を円滑にするための装具としてModifled Stirrup Brace(以下MSBと略す)を試作しその有効性を検討した。方法はErgometerを自由な速度で駆動する様に指示し, 1)装具無し, 2)装具装着の2条件の実験を行い, 下肢関節運動と筋活動を分析した。装具無しでは患側下肢足clonusの出現によりpedal回転運動が妨害され円滑な連続運動が不可能であったが, 装具により足関節をcontrolすることで足clonusが抑制され円滑な連続回転運動が可能となった。以上よりMSBは脳卒中片麻痺患者における自転車駆動の補助として有効であると考えられた。 This is a report of the effectiveness of modified Stirrup Brace (MSB) for hemiplegic patients in pedalling a bicycle ergometer. A chronic hemiplegic patient showing Brunnstrom stage IV in L/E, III in U/E and II in Finger, spastic muscle in L/E, was selected for the subject. The subject was ordered to pedal a bicycle ergometer (FITRON), first without MSB and then with MSB. Muscle activities of quadriceps femoris, hamstrings, tibialis anterior and gastrocnemius and articular joint movement of hip, knee and ankle were analyzed by surface electromyography and stick pictures by SONY Video Analysis System. In case of pedalling without MSB, ankle clonus of affected leg interfered continuous smooth movement and abnormal pattern of muscle activities of quadriceps femoris and gastrocnemius were recorded. In contrast, pedalling with MSB, the subject could pedal smoothly and no ankle clonus occurred, and those abnormal muscle activities disappered. From those findings, we concluded that MSB could be used as a device in pedalling bicycle ergometer for those hemiplegic patients who can not pedal continuously.